Gagasan Riffat Hasan tentang Kritik Gender atas Hadis Misoginis - Moh. Muhtador (Institut Agama Islam Negeri (IAIN) Salatiga, 2017)
Riffat Hasan is one of the Muslim feminists who againsts the strong patriarchal culture in her environment. Riffat Hasan’s idea of equality is a breath of fresh air for women who have been embraced by a growing patriarchal culture. As a Muslim feminist, Riffat hasan uses gender as an analysis to dismantle the construction of patriarchal culture covered with religious message, especially the hadith. The development of religious patriarchism is the result of interpretation of religious teachings that have the impression of misogynistic. Misogynistic interpretation model is one of the relationships that show the interaction of patriarchal culture with religion. The relationship forms a mutually supportive argument between religious teachings and patriarchal culture. So, both regions are understood as one unity. But as a critical effort on the development of religious patriarchism, Riffat Hasan’s idea of gender can be used as a medium for finding ideological constructs, and the use of epistemology in the understanding of religious teachings. Thus, the relationship of religion and patriarchal culture is no longer seen as a unity that must be obeyed thoroughly.